2020
DOI: 10.1097/mca.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol/apolipoprotein B ratio is superior to apolipoprotein B alone in the diagnosis of coronary artery calcification

Abstract: Objective Coronary artery calcification (CAC) is closely associated with adverse coronary artery events and mortality. Measuring the extent of CAC can lead to the early diagnosis of coronary artery atherosclerosis. In this study, we determined the association between the low-density lipoprotein cholesterol (LDL-C) and apolipoprotein B (ApoB) ratio, ApoB, and CAC and compared the usefulness of the LDL-C/ApoB ratio and ApoB for diagnosing CAC. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The wide acceptance of LDL-C coupled with the added expense and complication of measuring apoB has thus far prevented a major shift toward clinical application of plasma apoB at the point-of-care [ 275 , 276 ]. This may change as standardization of apoB measurement improves and as data supporting the benefits of apoB in cardiovascular health assessment accumulate [ 277 , 278 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wide acceptance of LDL-C coupled with the added expense and complication of measuring apoB has thus far prevented a major shift toward clinical application of plasma apoB at the point-of-care [ 275 , 276 ]. This may change as standardization of apoB measurement improves and as data supporting the benefits of apoB in cardiovascular health assessment accumulate [ 277 , 278 ].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of LAR has gained increased attention in recent years. Multiple studies [ 49 52 ] have indicated that LAR is associated with cardiovascular diseases and the development of cardiovascular diseases later in life. Drexel et al [ 22 ] recently reported that LAR can predict major adverse cardiovascular events in patients with preexisting atherosclerotic cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several other lipid-related parameters, including non-HDL-C ( 42 ), AC ( 12 ), LDL-C/HDL-C ( 43 ), LDL-C/ApoB ratio ( 44 , 45 ), and HDL-C/ApoA1 ratio ( 46 , 47 ), have also been reported to be associated with CVD risk. However, the results of the current study did not show an independent correlation between BMI and these indicators.…”
Section: Discussionmentioning
confidence: 99%